Is adjunctive perampanel beneficial for Lafora disease? - Stevanović, Galina; Jović, Nebojša; Kecmanović, Miljana (Vojnosanitetski pregled, 2021)
Backgrund/Aim. Lafora disease (LD) is progressive myoclonus epilepsy, characterized by intractable myoclonus and seizures, inevitable neurological deterioration, brutal cognitive decline and poor prognosis. The treatment still remains purely symptomatic. Recently, two single-case studies and one case series study reported the favourable effects of perampanel in LD. Our study aimed to test the benefits reported in three separate case studies. Methods. We performed an open label, prospective study of 4 patients aged between 22 and 34 years with mutation in NHLRC1 (EPM2B) gene, treated with perampanel (6–8 mg/day) as add-on therapy. Follow-up period comprised 14–26 months. Seizure frequency, myoclonus, functional disability and cognitive performance were analysed. Results. In 3 patients, both, seizures and myoclonus, showed remarkable improvement after the drug introduction (> 50% reduction). No significant effect was seen in one case. The functional and cognitive impairment maintained at the same level, though all patients were at the later stage of the disease. Psychiatric side effects were dose related. Conclusion. Our study supports the rare, previously reported observations that perampanel is beneficial in treating LD patients.